1973
DOI: 10.1021/jo00956a011
|View full text |Cite
|
Sign up to set email alerts
|

Selective reductions. XIX. Rapid reaction of carboxylic acids with borane-tetrahydrofuran. Remarkably convenient procedure for the selective conversion of carboxylic acids to the corresponding alcohols in the presence of other functional groups

Abstract: Aliphatic and aromatic carboxylic acids are reduced rapidly and quantitatively to the corresponding alcohols by borane in tetrahydrofuran, either at 0°or 25°. Even sterically hindered acids, such as 1-adamantanecarboxylic acid, dicarboxylic acids, such as adipic acid, phenolic acids, and amino acids undergo facile and quantitative reduction with borane. Aliphatic carboxylic acids are reduced at faster rates than aromatic carboxylic acids. Unlike more conventional, very powerful reducing agents, such as lithium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(96 citation statements)
references
References 4 publications
2
93
0
1
Order By: Relevance
“…For example, methyl (S)-3-(oxiran-2-yl)propanoate (1a) has been employed for the synthesis of many compounds such as elicitor [1], Streptrubin B [2] or chiral β-3-substituted homopropargyl [3], thiobutyrolactone [4], γ-hydroxyesters [5], diol-γ or δ-lactones [6], keto-esters [7], (+/´)-4-alkanolides [8] (Figure 1). Classically, epoxides such as 1a are obtained from (S)-γ-hydroxymethyl-γ-butyrolactone (2H-HBO, 2), itself derived from glutamic acid (Scheme 1) [9][10][11][12][13][14][15][16][17][18][19], a natural amino acid that is produced by fermentation on a commercial scale [20]. Glutamic acid is first deaminated to give the intermediate (S)-γ-carboxy-γ-butyrolactone, which was first reported by Austin et al using nitrous acid [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, methyl (S)-3-(oxiran-2-yl)propanoate (1a) has been employed for the synthesis of many compounds such as elicitor [1], Streptrubin B [2] or chiral β-3-substituted homopropargyl [3], thiobutyrolactone [4], γ-hydroxyesters [5], diol-γ or δ-lactones [6], keto-esters [7], (+/´)-4-alkanolides [8] (Figure 1). Classically, epoxides such as 1a are obtained from (S)-γ-hydroxymethyl-γ-butyrolactone (2H-HBO, 2), itself derived from glutamic acid (Scheme 1) [9][10][11][12][13][14][15][16][17][18][19], a natural amino acid that is produced by fermentation on a commercial scale [20]. Glutamic acid is first deaminated to give the intermediate (S)-γ-carboxy-γ-butyrolactone, which was first reported by Austin et al using nitrous acid [11].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the third and last route consists of a one-step reduction of the carboxylic acid into the alcohol in presence of borane-methylsulfide (BH3-Me2S) [3,17] or borane-THF [18]. It is noteworthy that the substitution of borane-methylsulfide by borane-THF to obviate odor problems on large scale [12,19] resulted in over-reduction to the lactol [16]. Although these three routes provide 2 in good yields, they either require two steps or use a carcinogenic reagent (i.e., BH3-Me2S).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vinylic halides substituted at the a-position provided mixed results. 2-Iodo-1-hexene or a-iodostyrene both gave little or none of the desired products in the reaction with 1-heptene and morpholine (entries 21 and 22), while 2-bromopropene produced the desired product in high yields (entries [24][25][26][27]. However, in all of these cases with asubstituted halides, the nucleophile attacked exclusively at the less hindered end of the kallylpalladium species.…”
Section: C) ^ C) La Lbmentioning
confidence: 99%
“…His results indicated that in some cases vinylic triflates give better yields than vinylic iodides. With this in mind, 2-methyl-1 -propenyl triflate was allowed to react with 1,5-hexadiene and several carbon nucleophiles (entries [26][27][28]. In all cases, the reactions led to a single product in moderate yield.…”
Section: Cross-coupling With Carbon Nucleophilesmentioning
confidence: 99%